Human rights in the context of gender and juvenile policy in different legal systems - Пережняк, Борис Аркадійович; Пережняк, Б. А.; Пережняк, Борис Аркадиевич; Perezhniak, Boris; Perezhniak, Borys A.; Мельничук, Ольга Степанівна; Мельничук, О. С.; Мельничук, Ольга Степановна; Melnychuk, Olha S.; Матійко, Микола Володимирович; Матійко, М. В.; Матийко, Николай Владимирович; et al. (Universidad de la Amazonia, 2021)
The study aims to identify the features of gender and juvenile policy in different legal systems and the formation of women's and children's rights. At present, equal rights are one of the main tasks of the modern social and legal state, as equality of rights and non-discrimination have been proclaimed by many constitutions and enshrined at the international level. The implementation of an effective gender and juvenile policy will increase the state's reputation in the international arena and ensure a high degree of trust in the government.Given the differences in the development of this aspect of countries from different legal systems, the analysis of the specifics of ensuring rights within gender and juvenile policy will further improve existing ways of regulating gender and juvenile relations by borrowing the main promising ideas and provisions underlying public policy. To conduct a research the authors used different scientific methods. Among these methods are the analysis and synthesis, the formal-legal and the comparative law method. The result of this work is to identify specific features characteristic of gender and juvenile policy of different legal systems, determine the importance of human rights and non-discrimination, offer effective ways to improve the implementation of gender and juvenile policy on the example of progressive states.

Дослідження направлене на виявлення особливостей гендерної таювенальної політики в різних правових системах та становлення прав жінок та дітей. Наразі урівняння в правах є однією з основних завдань сучасної соціальної та правової держави, оскільки рівність прав та недопущення дискримінації проголошені багатьма конституціями та закріплені на міжнародному рівні. Здійснення ефективної гендерної та ювенальної політики дозволить підвищити рівень репутації держави на міжнародній арені та забезпечить високий ступінь довіри до влади. З огляду на відмінності у розвитку в даному аспекті держав з різних правових систем, аналіз особливостей забезпечення прав в межах гендерної та ювенальної політики дасть змогу подальшого удосконалення існуючих шляхів урегулювання гендерних та ювенальних правовідносин через запозичення основних перспективних ідей та положень, покладених в основу відповідної державної політики. Для проведення дослідження автори використовували різні наукові методи. Серед цих методів - аналіз та синтез, формально-правовий та порівняльно-правовий метод. Результат проведеної роботи полягає у виявленні специфічних рис, характерних для гендерної та ювенальної політики держав різних правових систем, визначення важливості дотримання прав людини та недопущення дискримінації, запропонуванні ефективних способів удосконаленняздійснення гендерної та ювенальної політики на прикладі прогресивних держав.
Perezhniak B. Human rights in the context of gender and juvenile policy in different legal systems / B. Perezhniak, O. Melnychuk, M. Matiiko, H. Kotyk, N. Mokhd // Amazonia Investiga. – Vol. 10. - Issue 38. - Universidad de la Amazonia, 2021. – Р. 138-147.
Keywords: gender and juvenile policy; gender; principle of equality; principle of non-discrimination; gender gap index; гендерна та ювенальна політика; гендер; принцип рівності; принцип недискримінації; індекс гендерного розриву; Research Subject Categories::LAW/JURISPRUDENCE